Probing heteronuclear (15)N-(17)O and (13)C-(17)O connectivities and proximities by solid-state NMR spectroscopy. - Hung, I; Uldry, A; Becker-Baldus, J; Webber, A; Wong, A; Smith, M; Joyce, SA; Yates, JR; Pickard, C; Dupree, R; Brown, S (2009)
Heteronuclear solid-state magic-angle spinning (MAS) NMR experiments for probing (15)N-(17)O dipolar and J couplings are presented for [(2)H(NH(3)),1-(13)C,(15)N,(17)O(2)]glycine.(2)HCl and [(15)N(2),(17)O(2)]uracil. Two-dimensional (15)N-(17)O correlation spectra are obtained using the R(3)-HMQC experiment; for glycine.(2)HCl, the intensity of the resolved peaks for the CO and C-O(2)H (17)O resonances corresponds to the relative magnitude of the respective (15)N-(17)O dipolar couplings. (17)O-(15)N REDOR curves are presented for glycine.(2)HCl; fits of the initial buildup (DeltaS/S < 0.2) yield effective dipolar couplings in agreement with (+/-20%) the root-sum-squared dipolar couplings determined from the crystal structure. Experimental (15)N-(17)O REAPDOR curves for the (15)N resonances in glycine.(2)HCl and uracil fit well to the universal curve presented by Goldbourt et al. (J. Am. Chem. Soc. 2003, 125, 11194). Heteronuclear (13)C-(17)O and (15)N-(17)O J couplings were experimentally determined from fits of the quotient of the integrated intensity obtained in a heteronuclear and a homonuclear spin-echo experiment, S(Q)(tau) = S(HET)(tau)/S(HOM)(tau). For glycine.(2)HCl, (1)J(CO) was determined as 24.7 +/- 0.2 and 25.3 +/- 0.3 Hz for the CO and C-O(2)H resonances, respectively, while for uracil, the average of the two NH...O hydrogen-bond-mediated J couplings was determined as 5.1 +/- 0.6 Hz. In addition, two-bond intramolecular J couplings, (2)J(OO) = 8.8 +/- 0.9 Hz and (2)J(N1,N3) = 2.7 +/- 0.1 Hz, were determined for glycine.(2)HCl and uracil, respectively. Excellent agreement was found with J couplings calculated using the CASTEP code using geometrically optimized crystal structures for glycine.HCl [(1)J(CO)(CO) = 24.9 Hz, (1)J(CO)(COH) = 27.5 Hz, (2)J(OO) = 7.9 Hz] and uracil [(2h)J(N1,O4) = 6.1 Hz, (2h)J(N3,O4) = 4.6 Hz, (2)J(N1,N3) = 2.7 Hz].